PEMBINAAN KINERJA PEGAWAI NEGERI SIPIL DI DINAS PENDIDIKAN KOTA SURAKARTA - Novia Cahyaningrum; Andre N. Rahmanto; Tutik Susilowati (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2018)
The aims of the research are (1) To identify the realization of performance guidance toward civil servant in Department of Education Surakarta (2) To identify some problems happened during the realization of performance guidance toward civil servant in Department of Education Surakarta (3) To identify some efforts to overcome problems happened during the realization of performance guidance toward civil servant in Department of Education Surakarta. This research used qualitative research method. The kind of the research being used was case study research. The sources of data in this research were gained from informants, location of the event, and documents. The techniques of collecting data were gained by conducting interview, observation, and documentation. The data validity being used was triangulation method. Meanwhile, the data was analyzed by interactive analysis technique, where the data reduction, the data display, and the conclusion drawing were being related each other. The results of the research were (1) The realization of performance guidance toward civil servant in Department of Education Surakarta was based on the legal sources of law, either from the central or regional government has the same policy. The performance guidance toward civil servant was conducted through some programs which based on the guidance range, including giving general orientation, providing some facilities for the staffs, conducting some activities to fulfill both physical and spiritual needs, giving instruction for some work techniques, giving guidance on staffs’ abilities, giving guidance on civil servants discipline, and giving guidance through staff mutation. (2) There were some problems happened during the realization of performance guidance toward civil servant in Department of Education Surakarta, they were; the limitation of budget, the staff’s low response toward the follow-up guidance, and the reluctance feeling in guiding senior staffs. (3) Some efforts that had been attempted to overcome some problems on the realization of performance guidance toward civil servant in Department of Education Surakarta, were; proposing budget and training participants, conducting strict supervision, and using both oral warning and written media.